2005
DOI: 10.1149/1.1904983
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Behavior of a 4-Nitroimidazole Derivative

Abstract: A new synthesized compound, 1-methyl-4-nitro-2-hydroxymethylimidazole ͑4-MNImOH͒, was electrochemically reduced at the mercury electrode in aqueous, mixed, and aprotic media. In an aqueous medium, only one voltammetric peak was observed because of the four-electron, four-proton reduction of the nitro group to the hydroxylamine derivative in the 2-12 pH range. For the mixed and nonaqueous media, it was possible to observe a reversible couple due to the first one-electron reduction step of the nitro group to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
3
9
0
1
Order By: Relevance
“…In the Figure 2B, the Ep vs. pH plot shows that the peak potential is pH-dependent shifting to more negative potentials when pH increased. From these results we can observe that the obtained Ep values are very similar with the previously reported 21 for other 4-nitroimidazole analogue permitting to conclude that the change in the 2-position substitution did not change the reduction of the 4-nitroimidazole moiety. Furthermore from the comparison of the peak potentials between Hg and GCE we can assume that the reduction of nitroimidazole derivative is favoured on Hg.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In the Figure 2B, the Ep vs. pH plot shows that the peak potential is pH-dependent shifting to more negative potentials when pH increased. From these results we can observe that the obtained Ep values are very similar with the previously reported 21 for other 4-nitroimidazole analogue permitting to conclude that the change in the 2-position substitution did not change the reduction of the 4-nitroimidazole moiety. Furthermore from the comparison of the peak potentials between Hg and GCE we can assume that the reduction of nitroimidazole derivative is favoured on Hg.…”
Section: Resultssupporting
confidence: 88%
“…According to the well-known mechanism of 4-nitroimidazole derivatives 20, 21 we can assume that the observed irreversible peak in all the pH range is due to the four-electron, fourproton reduction of the nitroimidazole group to yield the hydroxylamine derivative according to the following overall reaction:…”
Section: Resultsmentioning
confidence: 99%
“…Another probable redox pathways for the studied molecules is conversion of the nitro group on the imidazolyl rings to NH 2 , NO, or NHOH. Experimental electrochemical studies on the nitroimidazolyl compounds also indicated the reduction of NO 2 functional group to nitro radical anion, nitroso, hydrohxylamine, and amine (36)(37)(38). Moreover, Metabolism study of 5-nitroimidazole in susceptible and resistant isogenic strains of Bacteroides fragilis by Carlier et al revealed the reduction of NO 2 functional group (39).…”
Section: Qsar Model From Electronic and Chemical Descriptorsmentioning
confidence: 99%
“…[28][29][30][31] In the first pathway (Equation (4) and (5)), reversible formation of one-electron nitro radical anion is followed by irreversible three-electron reduction. As the stability of ArNO 2 · is increased by the absence of In the second possible pathway (Equation (6) and (7)), four-electron reduction of NO 2 to NHOH (Equation (6)) and two-electron reduction of NHOH to NH 2 (Equation (7)) takes place.…”
Section: Electrochemical Behavior Of Aclonifen and The Influence Omentioning
confidence: 99%